Feasibility Study of a Proposed Sharia Cooperative in a Village Creative Economy: Evidence from Kampung Batik Cibuluh, Bogor - Fuad Haryanti; Resfa Fitri; Mohammad Iqbal Irfany; Daffa Aqomal Haq; Prima Gandhi (AL-MUZARA'AH, 2026)
This study examines the feasibility of establishing a Sharia-based Savings, Loan, and Financing Cooperative (KSPPS) to support the development of the creative economy in Kampung Batik Cibuluh, Bogor. Micro-enterprise actors in the area face limited access to sharia-compliant savings and financing services. Data were collected through surveys and in-depth interviews with community members and micro-business operators, which formed the basis for the willingness-to-pay analysis and a comprehensive feasibility assessment to evaluate interest in Islamic financial services. The findings indicate that 78.9% of respondents expressed interest in joining a sharia cooperative. Respondents were willing to contribute IDR 31,998 for principal savings and IDR 15,442 for mandatory savings, with a financing service margin of 29.5%. The financial analysis produced an NPV of IDR 675,985,915, an IRR of 16.2%, and a payback period of seven years, indicating that the KSPPS initiative is financially viable. The non-financial assessment suggests that the initiative can be implemented by considering community acceptance and social factors. Overall, the establishment of a sharia cooperative in Kampung Batik Cibuluh is considered feasible both financially and non-financially, and the study provides insights into the application of sharia-based financial services in a Muslim-friendly tourism village while highlighting their relevance for similar community-based economic contexts.